IMPROVING STUDENTS’ SPEAKING SKILLS BY USING PICTURE-CUED MEDIA TO THE EIGHTH GRADE STUDENTS OF SMP SANTO YOSEPH MEDAN - Simamora, Julia Marito; Sembiring, Novalina; Pangaribuan, Jontra Jusat (Kairos English Language Teaching Journal, 2020)
Speaking is considered as an important skill to be accomplished by students. As a language is used as a tool of communication, the ability of speaking or communicating with others takes an important role. People should know how to express thoughts, opinions, feelings, and ideas through the language. Teachers can also use media to enable the students to present ideas to individual peers, peers group, and entire classes. For example, students learn to speak on a subject of their own choice or on the teacher’s topic through picture-cued media. This study is a Classroom Action Research which focuses on improving students’ speaking skills by using picture-cued media. The teaching process was carried out in two cycles. The data consist of observation sheet and test. The data from the observation that have been taken from every cycle are analyzed descriptively, while the data from test are analyzed quantitatively. The result of this study shows that using picture-cued media can improve students’ speaking skill. This is proven by students’ test score that improved in each test. In the pre-test, the students’ average score is 53.8. While in the formative test cycle I, the students’ average score is 61.58, and in the post-test cycle II, the students’ average score is 78.8. That means the picture-cued media can improve the students’ speaking skill significantly. In this research, it is recommended that if the students are not confident in their speaking skills, the students can be given chances to prepare. Teachers are recommended to provide the interesting picture-cued media, control the students’ activities in the classroom, give clear instructions and give chances to practice their English as frequently as possible by using picture-cued media.